Celebrity, scandal and the male athlete: a sport media analysis. Issue 3 (26th May 2016) - Osborne, Angela; Sherry, Emma; Nicholson, Matthew
ABSTRACT: Research question: This study contributes to the understanding of scandal in the context of elite team sport through an analysis of print media coverage of off-field instances of athlete misbehavior. Print media coverage is indicative of the types of incidents warranting primary consideration by media and sports organizations. The research questions were: What types of incidents of poor off-field behavior by male athletes are most likely to attract print media attention? What is the relationship between frequency of media attention of types of off-field misbehavior and status of the athlete? Research methods: A data set of print media coverage, drawn from eight Australian newspapers with circulation of over 100, 000, of professional male athletes' off-field misbehavior in all sports ( n = 1868), collated over a six-month period, was analyzed. Coding of evaluative language was used to determine the status of the incident as representing off-field misbehavior. Descriptive statistics were used to determine the frequency of media attention paid to which types of behaviors. A news values framework was applied to draw out aspects elevating these items' newsworthiness. Results and findings: Analysis revealed the news value of the 'celebrity' athlete contributed significantly to frequency of media attention. Celebrity status, in concert with any other news value, was primarily influential in determining frequency of articles appearing in newspapers. Implications: A strategic, staged approach to manage celebrity and visibility – based on incorporating media management, public relations and relationship management principles and integrated across functions – is recommended.